Farm-forestry in the Peruvian Amazon and the feasibility of its regulation through forest policy reform - Sears, R.; Cronkleton, P.; Villanueva, F.P.; Ruíz, M.M.; Pérez Ojeda del Arco, M. (Elsevier, 2018)
In 2015 the Peruvian government launched a new set of regulations associated with the forest law aimed to increase competiveness of the timber sector, ensure the conservation and sustainable production of timber on public and private forestlands, and improve rural livelihoods. Small-scale timber producers have been marginalized in the sector in the past, and the new regulations claim to provide pathways to formalization for these actors. We draw on policy analysis and field research in the central Amazon region of Peru using mixed methods to characterize smallholder on-farm timber production and evaluate the feasibility of the new regulatory mechanisms for formalizing small-scale timber producers. Through examining a case study on the production and sale of the fast-growing pioneer timber species Guazuma crinita, locally known as bolaina, we found a diversity of management practices, with the strongest reliance on natural regeneration in agricultural fallows, an informal supply chain, and no case of formal documentation at time of sale. We assessed that none of the new regulatory mechanisms will accommodate the sale of timber produced in agricultural fallow stands. We recommend the inclusion of fallow timber in the new forest plantation registry, which could result in the formalization of the supply chain and create an incentive to increase production by small-scale producers.